Making a Difference Across Kansas, K-State Research and Extension Programming Report 2022-23 - Hadley, Gregg (My University, 2024)
K-State Research and Extension's program report for 2022-2023. This report to a variety of stakeholders illustrates the statewide extension work for the programming year.
RPT112_2024_02
Keywords: RPT112; Administrative and Research Reports